Post-Eruption Lava Dome Emplacement Measured by UAV Photogrammetry: An Investigation One Year After The 2017-2019 MT. Agung Eruptions - Andaru, Ruli (2022)
We present an observation of morphological changes at Mt. Agung lava dome one year after the 2017-2019 eruption crisis using UAV-photogrammetry method. Five time-series UAV datasets involve the images collected during the crisis period and the newest data collection (July 16, 2020) were used to provide a detailed investigation of the changes in morphology inside the crater and land cover on the surrounding slopes. The digital surface models (DSMs) generated by structure-from-motion (SfM) with multi-view stereo (MVS) algorithm were used to quantify the dome growth, the surface emplacement, and the actual remaining deposited material eruption surrounding the summit. Analysis of the last two series orthoimages indicates that the crater surface's texture remarkably unchanged one year after the eruption crisis (the dome still presents rough surfaces that resemble small stones and sand). According to the DSMs difference, it is evident that there were no considerable surface displacements inside the dome. It implies that no significant magma pressure accumulation occurring the dome. However, we found a small-scale growth in the central dome, which has increased the dome height up to 2 m and inflate the dome with a volume of 45,950 m3. We have also observed a new lava lake (e.g., compound lava) with an area of 9,166 m2 in the southeast of the dome edge. This new lava lake uplifts the surface up to 29 m and translated to a 79,623 m3 additional volume. Meanwhile, the depression areas surrounding the central dome were observed with a depth between 0.5 and 4 m. The amount of material deposited on the volcano's summit was identified with a total volume of 2.93 × 106 m3. This remaining deposited volume could be a potential lahar in the future. The ability to measure spatial and time-series of the lava dome changes from SfM-UAV, therefore, provides effective, detailed, and sometimes sole means of observing and quantifying dome surface emplacement in the period of before, during and after eruptions. © 2022. International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences - ISPRS Archives. All rights reserved.